Medium and Message: Globalization and innovation in the production field of Indian fashion. Issue 6 (June 2016) - Khaire, Mukti; Hall, Erika V.
How do unconventional innovations become accepted in creative industries? To uncover the process by which conventions changed in the field of Indian fashion, we analysed the content of all 586 articles on fashion published in India's leading fashion magazine during a 20-year period. The results of this exploratory analysis indicate that a regulatory change triggered economic liberalization in India, and the resultant globalizing forces facilitated interdiscursivity in the fashion media. As a result, the conventions of the global fashion paradigm permeated the Indian media discourse, gained acceptance, and came to co-exist with the previous "local" model of fashion and its conventions. This process increased the visibility of innovations that were previously peripheral in the field. The findings offer initial insights into the processes of change in creative industries, which are characterized as being relatively difficult to alter. The results have implications for organizational research in the areas of creative industries and innovation.